Multi-image production packet. - Eastman Kodak Company (Rochester : Motion Picture and Audio-visual Markets Division, Kodak, 1980)
A select group of data books, pamphlets, and periodicals to help meet the needs of producers of multi-image programs.
Keywords: Slides (Photography); Lantern projection